Perbandingan Nilai Kedalaman Relatif Sungai Brantas Kabupaten Jombang dengan Perhitungan Algoritma Van Hengel and Spitzer Citra Sentinel-2 dan Digital Elevation Model (DEM) - Niswah Selmi Kaffa; Muchammad Masykur; Yoga Kencana Nugraha (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
Shallow water relative depth can be gained from the Digital Elevation Model (DEM). As science develops, methods are developed to gain the relative depth one is by processing the Sentinel-2 image using Van Hengel and Spitzer algorithm. The authors aim to compare the relative depth gained from the Sentinel-2 image using the Van Hengel and Spitzer algorithm to the relative depth gained from DEM. The data needed are orthorectified Sentinel-2 level 1C images downloaded from the Earth Explorer page and DEM downloaded from the Tanah Air page. Sentinel-2 image is then corrected atmospherically and radiometrically to get its radian value then processed using the Van Hengel and Spitzer algorithm. The sample points are spread at 25 meters intervals along the Jombang regency Brantas River. This study only compares the computational calculation therefore no field validation is carried out. Sentinel-2 Van Hengel and Spitzer provides an average relative depth of 16.35 m and DEM provides an average relative depth of 17.98 m with the determination coefficient (correlation value) of the two data is 6.52%. The low correlation is due to the high sediment content in the water column of Brantas River, causing the bias in the image.